2022
DOI: 10.3390/s22072443
|View full text |Cite
|
Sign up to set email alerts
|

ARACAM: A RGB-D Multi-View Photogrammetry System for Lower Limb 3D Reconstruction Applications

Abstract: In the world, there is a growing need for lower limb prostheses due to a rising number of amputations caused primarily, by diabetic foot. Researchers enable functional and comfortable prostheses through prosthetic design by integrating new technologies applied to the traditional handcrafted method for prosthesis fabrication that is still current. That is why computer vision shows to be a promising tool for the integration of 3D reconstruction that may be useful for prosthetic design. This work has the objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…This cast is then removed and filled with plaster to obtain a positive mold as described by Chen et al 6 The prosthetist ensured that the mold was physically modified in shape and size and patient-specific information was de-identified prior to sharing both with this research team, this positive mold is shown in Figure 2(a). To obtain the computational model shown in Figure 2(b) a multi-view setup proposed by Barreto et al 15 was used to 3D-scan the plaster-cast mold. This system uses five multiple color and depth consumer-grade cameras arranged in a radial array.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This cast is then removed and filled with plaster to obtain a positive mold as described by Chen et al 6 The prosthetist ensured that the mold was physically modified in shape and size and patient-specific information was de-identified prior to sharing both with this research team, this positive mold is shown in Figure 2(a). To obtain the computational model shown in Figure 2(b) a multi-view setup proposed by Barreto et al 15 was used to 3D-scan the plaster-cast mold. This system uses five multiple color and depth consumer-grade cameras arranged in a radial array.…”
Section: Methodsmentioning
confidence: 99%
“…The ARACAM system has proven to be useful in design and fabrication applications for transtibial or transfemoral lower limb prostheses. 15…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-view stereo (MVS), a significant field in computer vision, intends to reconstruct 3D models with dense representations from multi-view images and related internal and external camera parameter matrices. The research results of 3D reconstruction have been frequently used in robot navigation [ 1 , 2 ], augmented reality [ 3 ], and photogrammetry [ 4 , 5 ]. High-resolution images allow for better reconstruction, but such large-size images consume a lot of processing resources and time.…”
Section: Introductionmentioning
confidence: 99%
“…Scanning systems based on the photogrammetry technique are of interest to many industries. In the field of human scanning, it is possible to mention, among others, virtual fitting rooms [ 7 ], fitness and sport [ 8 ], education [ 9 ], as well as health and medicine [ 10 , 11 , 12 , 13 , 14 ]. Typically, as a result, the scanning of stationary models has been obtained, although attempts have also been made to create interactive models, which may be used, for example, in the education of anatomy [ 15 ].…”
Section: Introductionmentioning
confidence: 99%